2020
DOI: 10.1080/16070658.2020.1741903
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Mini Nutritional Assessment tool among an elderly population in Yeka sub-city, Addis Ababa, Ethiopia

Abstract: Background: The widely used nutritional assessment tool used for the elderly includes the Mini Nutritional Assessment (MNA) and Mini Nutritional Assessment-Short Form (MNA-SF) tool. These tools have not been evaluated for their validity and reliability among the elderly population of developing countries such as Ethiopia. This study aimed to evaluate the reliability and validity of the full and short form of the Mini Nutritional Assessment tool among the elderly in Ethiopia. Method: We evaluated the reliabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…The previous studies in Ethiopia showed the same outcome: body weight, BMI, MUAC and CC had a significant positive correlation with MNA-SF total score. 44 This demonstrates the utility of the MNA-SF for evaluating nutritional status, as it is easy and available for use in OPD and community settings, and it correlates with many anthropometric measurements. However, the previous studies demonstrated that WC, HC, WHtR, WHR were common used in the screening risk of cardiovascular disease more than used for screen risk of malnutrition.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The previous studies in Ethiopia showed the same outcome: body weight, BMI, MUAC and CC had a significant positive correlation with MNA-SF total score. 44 This demonstrates the utility of the MNA-SF for evaluating nutritional status, as it is easy and available for use in OPD and community settings, and it correlates with many anthropometric measurements. However, the previous studies demonstrated that WC, HC, WHtR, WHR were common used in the screening risk of cardiovascular disease more than used for screen risk of malnutrition.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies in Ethiopia showed the same outcome: body weight, BMI, MUAC and CC had significant positive correlations with full MNA score. 44 , 47 A correlation between MNA score and the handgrip test was only found for the full MNA. A previous study in Indonesia showed the same outcome: the handgrip test demonstrated a significant positive correlation between handgrip strength and nutritional status as determined by the full MNA.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The ndings of this study employed validated tool with overall accuracy of 91% (sensitivity and speci city of 87.9% and 89.6% for the established cutoff points) [33]. It also employed valid and reliable anthropometric measurements for better outputs.…”
Section: Discussionmentioning
confidence: 93%
“…The sensitivity and specificity of the MNA ® are 80% (SD 13) and 68% (SD 22), respectively, against a wide range of criteria in 40 studies (see table 15: MNA ® Sensitivity/Specificity against Nutritional assessment parameters & other parameters) (140,222,227,228,235,241,246,248,. The same is true for the MNA ® -SF with a sensitivity of 87% (SD 10) and a specificity of 85% (SD 15) against the MNA ® , and a sensitivity of 81% (SD 18) and a specificity of 63 % (SD 20) against a wide range of criteria in 43 studies (Tables 16 & 17) (8,12,20,41,54,67,140,222,227,228,230,234,235,240,247,266,270,278,282,284,286,(288)(289)(290)(291)(292)(293)(294)(295)(296)(297)(298)(299)(300)(301)…”
Section: Mna ® Use In Clinical Researchmentioning
confidence: 99%